How important is industry-specific managerial experience for innovative firm performance? - Benjamin Balsmeier; Dirk Czarnitzki (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This study examines how industry-specific managerial experience affects firms' innovation performance in the context of different institutional environments. Based on firm-level data from 27 Central and Eastern European countries we identify a robust positive relationship between industry-specific experience of the top-manager and the decision to innovate as well as the share of new product-related sales. These effects are particularly pronounced for small firms operating outside the European Union or, more generally, in institutionally less developed countries. The results suggest that managerial experience affects firm innovations largely indirectly, for example, by reducing uncertainty about future returns on innovations or by providing knowledge about how to cope with institutional shortfalls potentially hampering the commercial success of new products.
urn:nbn:de:bsz:180-madoc-359313
Keywords: G38; L25; O32; P26; 330; Corporate Governance; Innovation; Managerial Experience